2009
DOI: 10.1111/j.1574-6941.2008.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of 13C labeling to assess carbon partitioning in transgenic and nontransgenic (parental) rice and their rhizosphere soil microbial communities

Abstract: Photosynthetic assimilation of CO2 is a primary source of carbon in soil and root exudates and can influence the community dynamics of rhizosphere organisms. Thus, if carbon partitioning is affected in transgenic crops, rhizosphere microbial communities may also be affected. In this study, the temporal effects of gene transformation on carbon partitioning in rice and rhizosphere microbial communities were investigated under greenhouse conditions using the 13C pulse‐chase labeling method and phospholipid fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 43 publications
(49 reference statements)
6
50
1
Order By: Relevance
“…The use of this marker as an indicator of fungal biomass is often debated, but, as we found a highly significant positive correlation between PLFA 18:2x6.9 and active fungal ITS copy number, we conclude that this marker is a useful indicator of fungal biomass in the rhizosphere, despite the presence of living roots (Frostegård et al, 2011). Earlier studies also showed that fungi quickly incorporate carbon from plants into their phospholipids (Lu et al, 2007;Wu et al, 2009;Drigo et al, 2010;Gschwendtner et al, 2011). Another large part (c. 9% of the total in the first sampling) of the total 13 C was detected in PLFA 16:1x5, mainly representing AMF (Olsson & Johnson, 2005;Denef et al, 2007).…”
Section: Active Microbial Communities In the Rhizospherementioning
confidence: 61%
See 2 more Smart Citations
“…The use of this marker as an indicator of fungal biomass is often debated, but, as we found a highly significant positive correlation between PLFA 18:2x6.9 and active fungal ITS copy number, we conclude that this marker is a useful indicator of fungal biomass in the rhizosphere, despite the presence of living roots (Frostegård et al, 2011). Earlier studies also showed that fungi quickly incorporate carbon from plants into their phospholipids (Lu et al, 2007;Wu et al, 2009;Drigo et al, 2010;Gschwendtner et al, 2011). Another large part (c. 9% of the total in the first sampling) of the total 13 C was detected in PLFA 16:1x5, mainly representing AMF (Olsson & Johnson, 2005;Denef et al, 2007).…”
Section: Active Microbial Communities In the Rhizospherementioning
confidence: 61%
“…It has been reported that carbon allocation within plants is strongly regulated by genotype and stage of development. Several studies (Milling et al, 2004;Götz et al, 2006;Griffiths et al, 2007;O'Callaghan et al, 2008;Weinert et al, 2009;Hannula et al, 2010) have provided information on the effects of transgenic crops on soil bacterial and fungal communities, but only a few have addressed the question from the carbon-partitioning perspective (Wu et al, 2009;Gschwendtner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results revealed that Bt-transgenic rice had little effect on dominant microorganisms essential for long-term sustainability of soil ecosystems. Wu et al (2009) studied soil microbial communities in the rhizosphere of Bt and non-Bt rice using phospholipid fatty acid analysis, and found that Bt rice had no persistent effect on microbial community composition in the rhizosphere. Other studies showed that the effects of GM plants on microbial communities are subject more to seasonal variations or to other environmental factors than to expression of Cry or other proteins (Fang et al 2005, Icoz et al 2008.…”
Section: Resultsmentioning
confidence: 99%
“…60, 2014, No. 9: 401-406 Plant Soil Environ. phospholipid fatty acid analysis with 13 C labeling (Wu et al 2009), denaturing gradient gel electrophoresis (Na et al 2011), terminal restriction fragment length polymorphism (Hannula et al 2012), next generation sequencing (Barriuso et al 2012). Only one report stated that the structures of soil bacterial communities of transgenic Bt maize, as determined by the single strand conformation polymorphism (SSCP), showed a significant difference (Baumgarte and Tebbe 2005).…”
Section: Resultsmentioning
confidence: 99%